Pattern of Expression of CDX2 in Colorectal Cancer and its Role in Prognosis: An Ambispective Observational Study - Singh, Jagdeep; Rajesh, N G.; Dubashi, Biswajit; Maroju, Nanda K.; Ganesan, Prasanth; Matta, Kiran K.; Charles, I; Kayal, Smita (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Caudal-type homeobox 2 (CDX2), a nuclear protein, is essential for the proliferation and development of intestinal epithelial cells and is frequently downregulated during tumorigenesis. CDX2 inhibits cell growth as well as stimulates differentiation by activating intestinal specific genes, thus lack of CDX2 favors tumor growth and aggressiveness.Objectives We aimed to evaluate the pattern of CDX2 expression in all stages of colorectal cancer (CRC) and study its association with baseline characteristics and prognosis.Materials and Methods Study was conducted as an ambispective observational study, enrolling cases of CRC retrospectively from January 2014 to July 2016 (30 months), and prospectively during next 18-month period till January 2018. We performed CDX2 staining by immunohistochemistry on the available biopsy blocks of CRC patients during the study period. Total 286 patients were registered during the study period, of which only 110 biopsy blocks were available for staining. CDX2 scoring was done by a semiquantitative method on whole tissue section for the intensity and percentage of the cells showing positivity. Correlation of CDX2 expression was done with baseline clinical and histopathologic characteristics, and survival.Results Of 110 patients, 77 (70%) constituted colon cancer and 33 (30%) were rectal cancer. The median age was 54.2 years, 62 (56.4%) being male and 48 (43.6%) female with male-to-female ratio 1.3:1. In the study cohort, 33 (30%) patients had stage II disease, 30 (27.3%) stage III, and 47 (42.7%) were stage IV. Seventy-three (66.4%) were positive for CDX2 and 37 (33.4%) were negative. Loss of CDX2 expression was significantly associated with advanced stage, rectal site, poor grade of differentiation, and presence of lymphovascular invasion (LVSI). With median follow-up of 16 months, progression-free survival (PFS) at 2 years was 30% for CDX2 negative patients compared with 67% for CDX2 positive (p = 0.009), while overall survival (OS) at 2 years was 46% for CDX2 negative versus 77% for positive patients (p = 0.01).Conclusion Loss of CDX2 expression is associated with advanced stage, higher tumor grade, presence of LVSI, and worse PFS and OS and thereby functions as a poor prognostic factor in CRC.
Keywords: colorectal cancer; CDX2; pattern; survival; prognosis